Cutaneous Blastomycosis Simulating Ganglionic Tuberculosis: A Case Report - Silva, Luanna Angélica Pesqueira e; Rolim Neto, Modesto Leite; Pita, Pablo (Amadeus International Multidisciplinary Journal, 2019)
Abstract: Blastomycosis is a chronic or subacute deep mycosis caused by a dimorphic fungus called Blastomyces dermatitidis, which usually produces pulmonary disease and, to a lesser extent, extrapulmonary forms such as cutaneous, osteoarticular, genitourinary, among others. Case Report: The authors report a case of primary cutaneous blastomycosis in Brazil, with characteristics that mimic ganglion tuberculosis. The diagnosis was confirmed by biopsy and histopathology. Conclusion: Cutaneous blastomycosis is clinically similar to ganglion tuberculosis, thus being an important differential diagnosis. Thus, knowing the characteristics and particularities of the disease, as well as its epidemiology, are important factors in the diagnosis of the disease. Keywords: Cutaneous blastomycosis, Ganglionic tuberculosis, Verrucous lesions.